A Temporary Immersion System to Improve Cannabis sativa Micropropagation - Rico, Saleta; Garrido, José; Sánchez, Conchi; Ferreiro-Vera, Carlos; Codesido, Verónica; Vidal, Nieves (Frontiers in Plant Science, 2022)
The aim of this study was to propagate axillary shoots of Cannabis sativa L. using liquid medium in temporary immersion bioreactors. The effect of the frequency of the immersion (3 or 6 immersions per day), explant type (apical or basal sections), number of explants (8, 10 and 16 explants), mineral medium (MS ½ nitrates, β-A and β-H, all supplemented with 2 μM metatopoline), sucrose supplementation (2%, 0.5% and 0% sucrose), duration of culture (4 and 6 weeks) and bioreactor type (RITA® and Plantform™) were investigated. As a result, we propose a protocol for the micropropagation of Cannabis apical segments in RITA® or Plantform™ bioreactors. The explants (8 per RITA® and 24 per Plantform™) are immersed for 1 min 3 times per day in β-A medium supplemented with 2 μM metatopoline and 0.5% of sucrose and subcultured every four weeks. This is the first study using temporary immersion systems in Cannabis sativa production, and our results provide new opportunities for the mass propagation of this species.